ACUTE DISSECTING ANEURYSM OF AORTA - Ahmad, Shakeel (Journal of Ayub Medical College Abbottabad, 1998)
This disorder is usually associated with medial degeneration of the aortic wall. This may be associated with Marfan syndrome or other collagen connective tissue disorders such as Ehlers Danlos disease. Dissection is classified as acute if it has been present less than 30 days or chronic if it has been present for longer. The dissection is also classified according to the site of intimal tear and to the degree of aorta involved. Using the DeBakey classification, type I and type II dissection begins just distal to the ostia of the coronary arteries and involves the ascending aorta. Type I dissection also extend into the thoracoabdominal aorta. Type III dissection begins just distal to the left subclavian artery and usually involve only the thoraco abdominal aorta, although on occasion they may extend in a retrograde fashion to involve the arch and ascending aorta. Iatrogenic dissection, caused by trauma from intraaortic manipulation with endovascular devices, now occurs more frequently than in the past.